Synthesis and testing of asynchronous circuits - micropipeline - Khaing, Kathy. (2008)
Regardless of how successful synchronous systems are, asynchronous design is an important research area since most of the asynchronous circuits provide higher performance. Since asynchronous circuits having no globally distributed clock, there are no problems about the clock skew occurring in synchronous systems. Micropipeline approach provides as a good powerful method to implement asynchronous circuits. This project focused into the concurrent testing of fourphase control structure along the pipeline. The proposed checker using doubleinput double-output D flip-flop (DIDODFF) allows stuck-at fault detection in the functional block or control structure of the micropipeline as well as the checker itself. The checker is designed to meet the Totally Self-Checking (TSC) goal based on the existing checker design concepts.